UJI DAYA TERIMA DAN NILAI GIZI BISKUIT YANG DIMODIFIKASI DENGAN TEPUNG BUAHPEPAYA (CARICA PAPAYA L.) - Ceni Dwi Ananda; Jumirah .; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Food diversification efforts can be done by using local food. Papaya is one of the local food with high nutrients and their availability of papaya fruit tends to increase every year. Papaya processed into flour  an effort to become snack food utilization. Biscuit flour papaya is a modification biscuit  by adding flour papaya fruit and its contains nutrients needed by the body. The purpose of this study is to determine the acceptability biscuit of papaya flour, organoleptic analysis based on taste, aroma, color, and texture of biscuit  papaya flour is determined using hedonic scale as well as to determine the nutrient content of papaya  biscuit flour. This study is an experimental study. Biscuit flour papaya fruit consists of two factors, wheat flour and papaya flour with 3 treatments. Each treatment uses a combination of papaya flour and wheat flour as much as 10%: 90%, 20%: 80% and 30%: 70% by symbols A1, A2, and A3. Panelists in this study are 30 students of SDN NO. 060923 Medan. The results showed that the organoleptic test results biscuit papaya flour most preferred based flavors and aromas are biscuits flour papaya 10% with a score of respectively 98,8% and 98,8%, while the papaya biscuit flour most favored by color and texture are biscuits flour papaya 20%  with respective scores of 98,8% and 90,0%. Based on analysis of the nutrient content of protein, crude fiber and calcium biscuit papaya flour which has the highest protein content is biscuits flour papaya 10% much as 6.91%, while the biscuit papaya flour which has the highest crude fiber content is biscuits flour papaya 20% as much as 4.26%, and biscuit papaya flour which has the highest calcium content is  biscuit flour papaya 30% as much as 9,53 mg/kg It is advisable in order to carry out further research on papaya flour biscuit  to improve the nutritional content and dissemination of information need to be made and received biscuits from  papaya flour is used as a snack food for school children. As well as the need to do further research to see the content of micronutrients contained in papaya flour biscuit. Keyword: papaya Flour, Biscuit, Acceptability, Nutrient content